Non-canonical functions of regulated cell death machinery regulate cellular growth, invasion and the interplay between cell death modalities - Shan, Y.; Mollereau, B. (Frontiers in Cell Death, 2024)
The exploration of multiple regulated cell death (RCD) pathways and the recognition that several cell death-related proteins, including caspases, serve non-canonical roles have significantly expanded and diversified cell death research. Caspases not only cleave cellular substrates, triggering apoptosis, but also impact essential processes such as cellular differentiation, proliferation, growth, and migration. These novel caspase-dependent regulatory networks are extensively studied during development, with Drosophila providing a diverse range of developmental models for investigating these phenomena. Moreover, recent insights into the non-canonical functions of cell death proteins have highlighted their pivotal role in cancer aggressiveness. Ultimately, understanding these non-canonical functions sheds light on the intricate connections between RCD pathways and their significance in promoting antioncogenic responses.